Oregano oil use in broiler diet increases accumulation of carvacrol and thymol in breast meat - Fidel Avila Ramos (Acta Universitaria, 2017)
Oregano oil is an aromatic used in poultry industry as a natural additive. This research was designed to quantify thymol and carvacrol in chicken breast meat. In total, 320 Broilers were fed on basal corn soybean meal diet contained crude soybean oil (CSO) or acidulated soybean oil (ASO) as a resource of energy with or without oregano oil (OO). Identification and measurement of compounds in meat was performed by gas chromatography (GC) and mass spectrometry (MS). Data obtained were transformed and analyzed parametrically, a signifi - cant increase of thymol and carvacrol was found in chicken breast meat supplemented with oregano oil ( p < 0.05). Breast meat of broilers fed with oregano oil and CSO accumulated more thymol and carvacrol: 333% and 366%, respectively. Breast meat of broilers fed with oregano oil and ASO accumulated thymol, but more carvacrol: 552% and 648% respectively, compared with control. In conclusion, oregano oil supplementation in diet increased deposi- tion of thymol and carvacrol in broiler meat.